Pilonidal Sinus: A Comparative Study of Open Versus Closed Methods of Surgical Approach - سليمان, جمال (Latakia University Journal -Medical Sciences Series, 2021)
Study Objective: To compare the outcomes of open and closed technique in surgical management of Pilonidal Sinus. Place and Duration of Study : Tishreen University Hospital,Lattakia,General Surgery Depatement from 1/1/2018 to31/12/2020. Study Design: Randomized control trial. Materials and Methods: A total of 65 patients with Pilonidal Sinus presented at general surgery Department were included Detailed history, general physical and systemic examination especially sinus area were done along with laboratory investigations. The patients were divided into two groups; patients in group I were managed by open technique and those in Group II were managed by closed technique. All patients were called for review at 01, 06, 12, 18 & 24 months interval to check for the recurrence and complications. The data was entered on SPSS 22.0 for analysis. Results: A total of 65 patients with Pilonidal Sinus disease were included in the study. Wound infection and dehiscence was found in 0.76% patients managed with close technique and in 5.17% patients managed with open technique. Similarly Recurrence rate in close technique were also found more i-e 12.06%while in Open technique only in 03.44%. Conclusion: The management of Pilonidal sinus is a surgical challenge. Both techniques are effective but the open technique is better option as compared to close technique because of low recurrence and wound dehiscence rate